THE EFFECT OF AUTOMOTIVE LABORATORY INFRASTRUCTURE ON STUDENT LEARNING SATISFACTION IN DIESEL MOTOR PRACTICUM COURSE IN MECHANICAL ENGINEERING STUDY PROGRAM PALANGKA RAYA UNIVERSITY - Pernando; Sri Murwantini; Ahmad Eko Suryanto (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2023)
In this study, regression analysis was used to examine the relationship between the availability of laboratory facilities and student satisfaction in the Mechanical Engineering Education program at UPR. The basic assumptions of the regression model were met, which included normality of residual distribution, homoscedasticity, and no autocorrelation. The test results showed that there was no heteroscedasticity and autocorrelation in this regression model, and the residual values had a normal distribution. In regression analysis, it is important to evaluate the significance of independent variables on the dependent variable. The test results showed that the predictor variable (availability of laboratory facilities) had a significant effect on the dependent variable (student satisfaction). An increase in laboratory facilities availability would contribute to a 1.162 increase in student satisfaction. The R-Square value of 0.637 or 63.7% indicates that 63.7% of the variation in student satisfaction can be explained by the availability of laboratory facilities, and the remaining is influenced by other variables not included in the model. This shows that the availability of laboratory facilities has a significant effect on student satisfaction. In conclusion, this study shows that the availability of laboratory facilities has a significant positive effect on student satisfaction in the Mechanical Engineering Education program at UPR. These findings can be used as input for the university to improve the availability of laboratory facilities to provide a better learning experience for students.